A dark and deadly journey - Kelly, Julia, 1986- (Kelly, Julia, 1986- Evelyne Redfern mystery, 2025)
"Evelyne Redfern returns in A Dark and Deadly Journey, the next book in international bestselling author Julia Kelly's captivating historical mystery series. After being sidelined for a pesky gunshot wound, typist-turned-field agent Evelyne Redfern is ready for her next assignment with Britain's secretive Special Investigations Unit. When a British Intelligence informant in Portugal mysteriously disappears just after hinting that he has vital information about German plans that could tip the balance of World War Two, Evelyne and her dashingly irksome partner, David Poole, are sent headed to Lisbon to find him. Once they land, Evelyne and David aren't even able to leave the airport, before she discovers one of their fellow aeroplane passengers murdered and uncovers a diary with a clear link between the victim and their missing informant. With their mission in jeopardy before it can truly begin, Evelyne and David fight to keep their cover intact as they descend deeper into the shadows that surround Lisbon's glittering collection of wealthy expats and dangerous spies. This case will test Evelyne and David's training, charm, and wit-and their growing attraction for one another"-- Provided by publisher.